EFFECTIVITAS OF RESTAURANT TAX RECEIPTS ON LOCAL NATIVE INCOME IN BARRU REGENCY - Masyitah; Musdalifa; Muhammad, Mukmin; Jaya , A.Ermi (Meraja journal, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal